1993
DOI: 10.1111/j.1432-1033.1993.tb18212.x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning from a mouse osteoblastic cell line of a set of transforming‐growth‐factor‐β1‐regulated genes, one of which seems to encode a follistatin‐related polypeptide

Abstract: Transforming growth factor(TGF)pl is a potent inhibitor of growth in mouse osteoblastic MC3T3-El cells. To isolate genes that are induced by TGFPl, the differential screening method was adopted using a cDNA library constructed from cells treated with TGFPl for 4 h. Six independent cDNA clones were isolated (TGFP-stimulated clone, TSC-5, TSC-36, TSC-115, TSC-128, TSC-160 and TSC-161), the expression of which was increased by TGFPl-treatment with maximal expression at 6-10 h. The steady-state levels of TSC-36, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
201
0
1

Year Published

1995
1995
2010
2010

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 247 publications
(208 citation statements)
references
References 43 publications
6
201
0
1
Order By: Relevance
“…Functional conservation of these properties are unclear however as Fstl1 lacks key BM-40 family characteristics such as calcium binding (Hambrock et al, 2004). Fstl1 is inducible by TGFβ (Shibanuma et al, 1993) and estrogen (Ohashi et al, 1997), and has been identified as a potential tumor suppressor (Hodgson et al, 2001). Expression of Fstl1 is reduced in human cancer cell lines (Hambrock et al, 2004;Mashimo et al, 1997;Sumitomo et al, 2000) and experimentally transformed cells (Johnston et al, 2000).…”
mentioning
confidence: 99%
“…Functional conservation of these properties are unclear however as Fstl1 lacks key BM-40 family characteristics such as calcium binding (Hambrock et al, 2004). Fstl1 is inducible by TGFβ (Shibanuma et al, 1993) and estrogen (Ohashi et al, 1997), and has been identified as a potential tumor suppressor (Hodgson et al, 2001). Expression of Fstl1 is reduced in human cancer cell lines (Hambrock et al, 2004;Mashimo et al, 1997;Sumitomo et al, 2000) and experimentally transformed cells (Johnston et al, 2000).…”
mentioning
confidence: 99%
“…Each assay was performed twice and three randomly chosen ®elds were analysed from duplicate wells in each assay a cysteine rich secreted heparin binding protein of 38 000 daltons, but little is known of its function (Zwijsen et al, 1994). Expression of exogenous TSC-36/Frp in K-Ras-transformed cells did not a ect their proliferation or morphology (Shibanuma et al, 1993). …”
Section: Tsc-36/frp Inhibits Invasion Of Fbrsmentioning
confidence: 99%
“…TSC-36/Frp was ®rst isolated due to its upregulation in response to transforming growth factor beta (TGFb) (Shibanuma et al, 1993) and down regulated in k-ras transformed ®broblasts and some human tumours (Mashimo et al, 1997). TSC-36/Frp is Western analysis of FBR-TSC6 and FBRNeo cell extracts to detect TSC-36-myc expression in cell extracts and cell supernatants.…”
Section: Tsc-36/frp Inhibits Invasion Of Fbrsmentioning
confidence: 99%
“…SPARC, the best-studied of the group, is known to regulate cell-matrix interactions and thereby regulate tissue remodeling and homeostasis (11). FRP has been reported to play some roles in cell-cycle inhibition and to have negative regulatory effects on growth in human lung cancer cells (8,16). However, the exact physiologic function of FRP remains to be clarified.…”
mentioning
confidence: 99%